Key Factors of Medium-High Frequency Oscillation in Chongqing-Hubei HVDC System and Suppression Strategies - Qinan LI; Yongjun XIA; Xiaolin ZHANG; Baokui SUN; Huadong SUN; Fan ZHANG; Lanfang LI; Yuefeng YANG; Qingtao HAN (Zhongguo dianli)
For the problem of medium and high frequency oscillations in flexible HVDC projects, the existing solution is to add a filter in the voltage feedforward path to suppress high frequency oscillations, which, however, increases the risk of medium frequency oscillations. For this reason, a method is proposed to avoid medium-high frequency oscillations by adjusting the control link delay based on the south channel of the Chongqing-Hubei flexible HVDC transmission project. Firstly, a impedance model of MMC converter station is established based on the principle of multi-harmonic linearization, and a comprehensive analysis is made on the influence of control link delay and grid voltage feedforward strategy on the impedance characteristics of MMC converter station and system stability. And then, the feasibility of adjusting the delay of the control link to avoid the medium-high frequency oscillation is discussed, and the method for selecting the time delay of the control link is given. Finally, based on PSCAD/EMTDC electromagnetic transient simulation, it is verified that the proposed method can achieve the suppression of the medium-high frequency oscillations in both the Hubei-side and Chongqing-side systems. Meanwhile, the proposed method has minor effect on the dynamic characteristics of the system.